Tổng quan về kế toán xanh qua phân tích trắc lượng thư mục - Nguyễn Phan Minh , Hòa; Nguyễn Thị Kim , Ngọc; Trương Hoàng Tú , Nhi; Đặng Thị Thu, Trang; Hoàng Văn, Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This paper aims to provide an overview of green accounting and indicates authors, sources, and countries that significantly impact this area. Drawing on a sample of 360 papers from Scopus and Web of Science, the authors analyze the publication trends on green accounting from 1992 to the third quarter of 2024. VOSviewer is used to perform the bibliometric analysis to identify outstanding authors, studies, and countries. The results indicate that scholars such as Cairns, Bartelmus, and Peter have made significant contributions to this topic. The United States, the United Kingdom, China, and Indonesia emerge as the countries with the highest number of citations and co-authorships. Additionally, the study identifies key keywords and emerging research themes related to green accounting. Future researchers can utilize this work to explore trends and topics related to green accounting. The study also anticipates that the number of publications in this area will continue to rise.